Efektivitas Program SMART POSTURE terhadap Peningkatan Pengetahuan Pencegahan Gangguan Muskuloskeletal pada Siswa SMK Roudlotul Hikmah: Effectiveness of the SMART POSTURE Program in Improving Knowledge of Musculoskeletal Disorder Prevention Among Vocational High School Students - Syafriansyah, Fahmi Essa; Riesmiyatiningdyah, Riesmiyatiningdyah; Kurdi, Tiara; Sujaka, Aditya Brahmantio; Nuraini, Nanik; Jannah, Zahrotul (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Musculoskeletal disorders (MSDs) among school-aged adolescents have become an increasingly important public health concern due to poor ergonomic practices, prolonged sedentary behavior, and excessive use of digital devices. Vocational high school students are particularly vulnerable because they engage in both classroom-based learning and practical activities that may increase the risk of musculoskeletal problems. Therefore, effective educational interventions are needed to improve awareness and knowledge of MSD prevention from an early age. This study aimed to evaluate the effectiveness of the SMART POSTURE (Student Movement Awareness for Reducing Tension and Posture Injury) program in improving vocational high school students’ knowledge of musculoskeletal disorder prevention. A one-group pretest–posttest design was employed. Twenty-six students from Roudlotul Hikmah Vocational High School were selected using purposive sampling. The SMART POSTURE intervention consisted of ergonomic education, demonstrations of correct posture, stretching exercises, and interactive discussions delivered in a single 90–120-minute session. Knowledge levels were assessed using a 10-item multiple-choice questionnaire administered before and after the intervention. Data were analyzed using descriptive and inferential statistics with a significance level of p < 0.05. The mean knowledge score increased from 58.27 ± 10.34 in the pretest to 85.19 ± 7.42 in the posttest, representing an improvement of 26.92 points. In addition, participants demonstrated improved ability to apply ergonomic sitting and standing postures, appropriate digital device usage, and proper school bag carrying techniques. High levels of participation and engagement were also observed throughout the intervention. The SMART POSTURE program effectively improved students’ knowledge and awareness regarding musculoskeletal disorder prevention. Integrating ergonomic education, practical demonstrations, and stretching exercises may serve as an effective health promotion strategy to foster ergonomic behaviors and support musculoskeletal health among adolescents.